Prevalence of steatotic liver disease, advanced fibrosis and cirrhosis among community-dwelling overweight and obese individuals in the USA - Yang, Alexander H; Tincopa, Monica A; Tavaglione, Federica; Ajmera, Veeral H; Richards, Lisa M; Amangurbanova, Maral; Butcher, Christian; Hernandez, Christie; Madamba, Egbert; Singh, Seema; Bettencourt, Ricki; Schnabl, Bernd; et al. (Gut, 2024)
BackgroundThere are limited prospective data among overweight and obese individuals on the prevalence of advanced fibrosis, and cirrhosis using advanced MRI-based methods in the USA. The aim of this study was to fill that gap in knowledge by prospectively determining the MRI-based prevalence of steatotic liver disease (SLD) and its subcategories, advanced fibrosis and cirrhosis among overweight and obese individuals residing in the USA.MethodsThis is a cross-sectional analysis of prospectively enrolled overweight or obese adults aged 40–75 years from primary care and community-based settings in Southern California. Participants were classified as having SLD if MRI proton density fat fraction ≥5%, and subclassified as metabolic dysfunction-associated steatotic liver disease (MASLD), metabolic dysfunction and alcohol-associated liver disease (MetALD) and alcohol-related liver disease (ALD) consistently with the new nomenclature guidance per AASLD–EASL–ALEH. Advanced fibrosis and cirrhosis were defined as magnetic resonance elastography (MRE) ≥3.63 kPa and MRE ≥4.67 kPa, respectively.ResultsThe cohort included 539 participants with mean (±SD) age of 51.5 (±13.1) years and body mass index of 32.6 (±6.2) kg/m2, respectively. The prevalence of SLD, advanced fibrosis and cirrhosis was 75%, 10.8% and 4.5%, respectively. The prevalence of MASLD, MetALD and ALD was 67.3%, 4.8% and 2.6%, respectively. There was no difference in prevalence of advanced fibrosis and cirrhosis among subcategories.ConclusionsUsing advanced MRI methods among community-dwelling overweight and obese adults, the prevalence of cirrhosis was 4.5%. Most common SLD subcategory was MASLD with 67% of individuals, whereas MetALD and ALD were less common. Systematic screening for advanced fibrosis among overweight/obese adults may be considered.